ANALISIS KOMPOSISI FOTOGRAFI PADA FOTO FASHION EDITORIAL ‘SWARNADWIPA’ KARYA NICOLINE PATRICIA MALINA - Aqila Fadia; Tulus Rega Wahyuni E; Tulus Rega Wahyuni E (JURNAL Dasarrupa: Desain dan Seni Rupa, 2022)
One of the activities to express yourself is through photography. Photography is not just an activity to take pictures or take pictures. However, expertise is also needed to be able to apply the basic techniques and composition of photography properly so that the resulting photos are more interesting. One Indonesian female photographer whose works are very interesting is Nicoline Patricia Malina. Nicoline is very famous for her Fashion Photography work. Nicoline's Fashion Photography works are usually used for editorial purposes. One of them is entitled 'Swarnadwipa'. In this photographic work, Nicoline uses a photographic composition of leading lines, symmetry, fill the frame, and the rule of third in portrait and landscape photo formats. Nicoline also uses a combination of gold tones which is a concept from the 'Swarnadwipa' photo series, and there are several other colors such as brown, black, gray and silver. Apart from that, Nicoline also used the Borobudur Temple building as a background for the 'Swarnadwipa' photo. This analysis uses a descriptive qualitative method, which aims to find out what photographic compositions are used in the 'Swarnadwipa' editorial fashion photo as well as to find out what the relationship between the photographic composition and the concept of 'Swarnadwipa'.